Applying waste heat recovery system in a sewage sludge dryer – A technical and economic optimization. (1st October 2016) - Tańczuk, Mariusz; Kostowski, Wojciech; Karaś, Marcin
Highlights: A modernization of waste heat recovery system in a sludge drying plant is proposed. Energy performance analysis rejected the downsize case of modernization. Optimal system sizes regarding Net Present Value and Net Present Value Ratio do not coincide. Up to 683 MW h/y of chemical energy savings for optimal heat exchanger size. Higher profitability for the larger heat exchanger cases: paybacks below 3.65 years. Abstract: Drying of digested sewage sludge, as an important alternative to sludge disposal at dumping sites, should comply with the requirements of high energy efficiency as well as economic feasibility. The technical and economic optimization analysis of installing a waste process heat recovery unit in a medium-temperature belt dryer operated in a municipal waste water treatment plant was carried out. Inlet capacity of the plant is 1.83 Mg of wet sludge per hour. The post-process air was indicated as a source of waste heat and the configuration of a heat recovery system was proposed. The main objective of the research was to find the optimal size of a chosen type of waste heat recovery heat exchanger for preheating ambient air to the process. The maximization of Net Present Value, and, alternatively, also Net Present Value Ratio were selected for the objective function of the optimization procedure. Simulation of yearly operation of waste heat exchanger was made for a range of different heat exchanging areas (101–270 m 2 ) regarding given parameters of a post-process air and different temperatures of ambient air. Energy performance of the modernization was evaluated and economic indices were calculated for each of the analyzed cases. The location of the maximum of optimization function was found and the calculations show higher profitability of the cases with larger waste heat exchanger. It can be concluded that the location of optimum of the objective function is very sensitive to the price of natural gas supplied to the system and less sensitive to the electricity price.